Targeting Eukaryotic mRNA Translation by Legionella pneumophila - Belyi, Yury (Frontiers in Molecular Biosciences, 2020)
Legionella is a gram-negative microorganism and an infectious agent of pneumonia in humans. It is an intracellular pathogen and multiplies in different eukaryotic cells like amoebae, ciliated protozoa, macrophages, monocytes and lung epithelial cells. Proliferation of L. pneumophila in eukaryotic cells depends on its type 4 secretion system, which delivers an arsenal of bacterial effector proteins to cytoplasm of its host. Once within the cytoplasm, effectors modify a broad range of host activities, including mRNA translation. Translation is inhibited by Legionella through the action of several effector proteins including Lgt1, Lgt2, Lgt3, SidI, LegK4, SidL and RavX. Lgt1-3 and SidI target elongation factors: Lgt1-3 mono-glucosylate elongation factor eEF1A, while SidI binds eEF1A and eEF1Bγ. Effector LegK4 inhibits protein synthesis by phosphorylating Hsp70 proteins, while SidL and RavX have no defined targets in protein synthesis machinery thus far. In addition to direct inhibition of protein synthesis, SidI also affects the stress response, whereas Lgt1-3 – unfolded protein response and cell-cycle progression of host cells. Whether manipulation of these processes is linked to canonical or non-canonical function(s) of targeted elongation factors remains unknown.